“Soccer can be inclusive”: cooperative learning in the teaching-learning of soccer in physical education - Pérez-Torralba, Alberto; Guijarro Jareño, Eva; Sierra de los Ríos, Juan Vicente; Evangelio, Carlos (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
A proposal for teaching-learning soccer is presented through techniques of Cooperative Learning (CL). Participants will be 52 students in 5th grade of Primary Education distributed in two groups-classes. Among these students, there are: 1) a boy with physical disability (single-leg amputee) who uses crutches for moving; 2) one boy and one girl from another country with difficulties in the knowledge and use of the Spanish language. The implemented lesson plan is composed of 12 structured lessons following the first two phases of the CL cycle (group creation and cohesion; and CL as content to teach and learn). The cooperative strategies used were: collective score, pairs-check-perform, challenge-challenge-trade, and PACER. Continuous and formative assessment will be linked to the learning process and the inclusion of all students.